Impacts of COVID-19 Pandemic on the Mental Health of Working Adults in the Czech Republic: Analysis of Self-Report Psychological Data in a One Year Perspective - Kučera, Dalibor; Stuchlíková, Iva; Mrhálek, Tomáš (European journal of investigation in health, psychology and education, 2021)
The article presents research evidence on psychological impacts of the COVID-19 pandemic on the economically active Czech population aged 18-64 (n = 1603; 365 men and 1238 women) within a one year perspective. The aim is to describe the differences in the reported mental health indicators (anxiety, depression, and distress) for women and men in the four age groups, two groups with different working statuses (continuation of work/interrupted working status), and between two phases of the epidemic (March to May 2020 and September 2020 to February 2021). The results point to elevated scores of negative mental health indicators (anxiety, depression, and distress) in different subgroups. More negative experiences in a pandemic situation were found, especially in groups of women, people under the age of 35, and among people with interrupted working status. The results also indicate a deterioration of symptoms over time during the epidemic.